Website-Based Digitalization as an Effort to Improve the Identification of Clinical Material Needs in Dental Health Laboratories - Kusasi, Edy; Rindharso, Rahmaisynta Putri; Sofian, Rizki (Center of Excellent (Pusat Unggulan Iptek), 2025)
Background: The problems encountered in identifying material needs in the Banjarmasin Dental Health Department laboratory are still carried out conventionally, namely by recording in books with the condition of students who increase every year so that the application of conventional systems is no longer effective to be implemented. This study aims to optimize the identification of website-based clinical material needs in the Banjarmasin JKG laboratory. This study uses the Research and Development (R&D) method with a model trial using the pre-experimental design one group prepost test method with purposive sampling. With a total sample of 50 people. The results based on the Willcoxon statistical test with a p-value of material needs identification before and after the application using the website of 0.000 <0.05 this shows that there is a difference in the effectiveness of identifying material needs before by 12.82 and after using the website by 15.44 there is an increase of 2.62. This means that the application of the website is more effective in identifying material needs compared to the previous system. The use of this new system presents data and information that can be utilized by users.